Effectiveness of Government Policies in Municipal Waste Management in Pekanbaru City, Riau Province, 2022 - Aulia Novri Rahmayanti (Journal of Applied Community Service and Innovation, 2025)
The persistent and poorly managed waste problem in Pekanbaru City raises public questions regarding the effectiveness of government policies in waste management and their implementation. The daily increase in population contributes directly to the rise in waste volume, with at least 1,100 tons of additional waste generated every day. Public participation also plays a significant role in the growth of waste volume. Citizens are expected to manage waste properly and understand the urgency of waste management. Furthermore, the community needs to recognize the importance of maintaining environmental cleanliness to safeguard public health. By providing the community with adequate understanding, it is expected that the amount of waste produced can be reduced. To assess the effectiveness of government policies in managing waste in Pekanbaru City, this study employs William N. Dunn’s policy effectiveness theory, which identifies five indicators of effectiveness: efficiency, adequacy, equity, responsiveness, and accuracy. In evaluating policy effectiveness, the government must determine whether a policy is efficient in achieving its intended objectives. This article utilizes a qualitative approach with a descriptive method.